2014
DOI: 10.1007/s10863-014-9591-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin remodeling: a regulatory hub for modulating cardiolipin metabolism and function

Abstract: Cardiolipin (CL), the signature phospholipid of mitochondria, is involved in a plethora of cellular processes and is crucial for mitochondrial function and architecture. The de novo synthesis of CL in the mitochondria is followed by a unique remodeling process, in which CL undergoes cycles of deacylation and reacylation. Specific fatty acyl composition is acquired during this process, and remodeled CL contains predominantly unsaturated fatty acids. The importance of CL remodeling is underscored by the life-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 133 publications
(207 reference statements)
0
90
0
Order By: Relevance
“…2016; Ye et al. 2016). In our study, we observed alterations in cardiac cardiolipin fatty‐acid species composition, namely a loss of the symmetric tetralinoleoyl‐CL in favor of more asymmetric cardiolipins with shorter and more saturated chains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Ye et al. 2016). In our study, we observed alterations in cardiac cardiolipin fatty‐acid species composition, namely a loss of the symmetric tetralinoleoyl‐CL in favor of more asymmetric cardiolipins with shorter and more saturated chains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CL is synthesized and remodeled within the mitochondria, but its precursors, phosphatidic acid and CDPdiacylglycerol, are formed primarily on the endoplasmic reticulum and are imported into the mitochondria where phosphatidylglycerol is synthesized ( 28 ). CL synthase then combines phosphatidylglycerol with the phosphatidyl group from a second molecule of CDP-diacylglycerol.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae lacking tafazzin, an additional deletion of the CL-specifi c phospholipase, Cld1, prevents the accumulation of MLCL, inhibits CL remodeling, and rescues the mitochondrial respiratory defect, strongly suggesting that the respiratory defect had been due to the accumulation of MLCL and/or the decrease in the total content of CL ( 25 ). In mammalian cells, two additional enzymes, lysocardiolipin acyltransferase 1 (AL-CAT1) and MLCL acyltransferase 1 (MLCL AT-1), can use acyl-CoAs to esterify MLCL ( 28 ). ALCAT1, however, is located on the ER, which would prevent its interaction with most CL ( 30 ), but MLCL AT-1 is present in mitochondria ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the decreased capacity of cells lacking tafazzin function to undergo mitophagy when stressed, a specific role for CL as a mitophagy initiator signal has emerged (Chu et al, 2014;Chu et al, 2013;Galbraith, 2014;Li et al, 2015;Ye et al, 2014b;Zhu et al, 2013). Recently, in rat cortical neurons, CL was shown to redistribute from the MIM to the MOM and then specifically bind to microtubule-associated protein 1 light chain 3 (MAP1LC3/LC3) upon mitophagy induction (Chu et al, 2013).…”
Section: An Enhanced Role For Mitochondrial Quality Control In Barth mentioning
confidence: 94%